Penerapan Model Pembelajaran Game Based Learning (GBL) Berbantuan Aplikasi Wordwall Pada Mata Pelajaran Ipas Untuk Meningkatkan Motivasi Siswa Kelas V SD - Yulia, Yulia; Amran, Muhammad; Khaerah, Ummul (Universtas Negeri Makassar, 2025)
The problem in this study is the low learning motivation of fifth-grade students in the IPAS subject. This study aims to determine how the implementation of the game based learning model assisted by wordwall media can improve students’ learning motivation in class V at UPTD SD Negeri 16 Parepare. The research used a qualitative approach with a classrom action research (CAR) method, conducted in two cycles. Data collection techiques includedd observation, questionnaires, and documentation. The research subject consisted of 1 teacher, 10 fifth-grade students, and 1 observer. The results showed an improvement in the learning process and students motivation. At the end of cycle l, teacher activity reached 83% (Good), student activity 63% (Fair), and student motivation 51% (Poor). In cycle II, teacher activity increased to 94% (Good), student activity to 81% (Good), and student motivation reached 81% (Excellent). It can be concluded that the Game Based Learning model with Wordwall media is effective in increasing students’ learning motivation in the Ipas subject.